Egypt's relations with Phoenicia (During the ancient and middle Egyptian states - 2780 / 1991 BC - khier, ameur (Journal of Social Sciences and Humanities, 2024)
The idea of the emergence between Egypt and the country of Phoenicia in the past was the subject of disagreement between historians in determining the time of its beginning. Some of them believed that it dated back to the third millennium BC, while others attributed it to the time of direct Egyptian control over the country of Phoenicia. So the aim of our research is to highlight the findings of recent studies to determine the path of rapprochement between the two parties, on one hand, and to refer to the archaeological evidences that were collected in both countries in order to clarify the motives of those relations, on the other hand. Then, we ask the following question: What were the motives of the Egyptians’ communication with the Phoenicians in the past, and what were the contributing factors to that ? And how was the nature of relations between the two parties during the stages of Pharaonic rule ? Recent studies have proven that the historical roots of the Egyptian-Phoenician relations were situated in the distant periods that preceded the dynastic era in Egypt, and that the interest of the Egyptians in the land of Phoenicia was purely economic and for security interests. More, the ports of communication between Egypt and Phoenicia (through the Sinai and through the Mediterranean coast) contributed to strengthening commercial ties which were among the general phenomena of the Phoenicians with the geographical neighboring areas, especially with Egypt during the third and second millennium BC. And, trade has been active and expanded between the two parties to include the political field and other civilization aspects